Non-linear modeling for low and high power microwave transistors - Rafael Valdivia, Guillermo (2017)
New generation of communications systems will demand the use of low power devices in mesh configuration. This work presents a new characterization procedure for those devices in order to predict their behaviour before the implementation saving time and cost.